Applied supervised learning with Python use scikit-learn to build predictive models from real-world datasets and prepare yourself for the future of machine learning - Johnston, Benjamin; Mathur, Ishita (Packt Publishing Ltd, 2019)
Applied Supervised Learning with Python provides you a rich understanding of machine learning, one of the most pursued topics in information science, and Python, one of the most popular scripting languages. Through this book, you'll learn Jupyter Notebooks, the technology used in academic and commercial circles with in-line code running support.
Includes bibliographical references and index. - Online resource; title from digital title page (viewed on May 15, 2019)
Keywords: Python (Computer program language); Python (Langage de programmation)